Comparative study of anterior knee pain after patelloplasty with and without circumferential denervation in a total knee arthroplasty - Al-Shamari, Ahmed Latteef (AL-Kindy College Medical Journal, 2019)
Background: The anterior knee pain is an important chief complaint of the patients with knee osteoarthritis due to patellofemoral pathology. The pain receptors denervation can be achieved by circumferential denervation of the patellar area by a process of electrocautery. Objectives: The aim of current study is to assess the pain after total knee arthroplasty (TKA) by patelloplastywith and without circumferential denervation via electrocautery at a minimum follow up with 1 year separately for each patient. Type of the study:Cross- sectional study. Methods: Thirty five patients,with mean age of about (62.8) years, were enrolled in this prospective, hospital based study that was held at Al-Yarmouk Teaching Hospital in Baghdad from October 2012 to November 2016. These patients were divided into 2 groups, first group was composed of 19 patients who have TKA with patellar circumferential denervation by electrocautery with patelloplasty by removing peripheral osteophytes of patella , the second group of 16 patients were undergone TKA without denervation, but only patelloplasty. The second group was considered as the control group. Visual analogue scale (VAS) was used to evaluate pain pre and post operatively. The patient’s functional ability was assessed by knee society score (KSS) also before and after TKA for both groups and pain killer was given according to patients need. Results: All of the patients were followed for 12 months period. No drugs were used other than occasional use of pain killers in first month after operation for all patients in group one of study. On VAS scale, significant statistical difference in pre and post-operative scales were noticed between both groups of study. The Knee Society Scale (KSS) was showing a non- significant statistical significance between both study groups before and after TKA. ConclusionA: nterior knee pain can be reduced through the use of patelloplasty with circumferential denervation of patella byelectrocautery, compared with non- denervated procedure. Good clinical outcome was also present.